Prescribers' experiences of, and attitudes to, use of morphine for palliative care at a tertiary hospital in Zambia. Issue 2 (14th March 2020) - Robertson, Emma; Bambala, Andrew; Kalungia, Aubrey C.; Marshall, Sarah; Mbozi, Patience; Munkombwe, Derick
ABSTRACT: Objective: To explore medical doctors' experiences of, and attitudes to, use of morphine for palliative care at a tertiary hospital in Zambia. Methods: A qualitative, exploratory case study was undertaken. Semi-structured interviews were used to collect data from 14 medical doctors working in the fields of oncology, pediatrics, and internal medicine at a tertiary hospital in Lusaka, Zambia, regarding their experiences and attitudes to prescribing morphine for palliative care. Thematic analysis of interview transcripts was carried out to establish common themes in the data. The study was approved by BSMS and UNZA research ethics committees. Results: All participants agreed that doctors were becoming more comfortable with the prescribing of morphine, although experiences were notably different for doctors working in oncology, compared to other departments. Themes of difficulty discussing end-of-life, poor recognition of pain, and fear of patient addiction, were more prominent in the responses of non-cancer doctors. Morphine use was generally restricted to cancer and sickle cell disease patients, with most non-cancer doctors stating that they rarely prescribe morphine for outpatient use. Training in pain management and the presence of a palliative care team were perceived to be facilitators to morphine prescribing. Conclusions: Although there is an increased willingness to prescribe morphine, limited knowledge of pain management, especially for nonmalignant disease, underlies many of the findings in this study. Opportunity exists for professional development in pain management to further improve the acceptance and use of opioids in palliative care, especially for out-patients.